Capsular Contraction with S‐Shaped Deformity of Nonlength‐Expanding Inflatable Penile Prosthesis Cylinders: Management and Prevention Strategies. Issue 2 (10th October 2013) - Karpman, Edward; Henry, Gerard
Abstract Introduction Capsular contraction (CC) occurring with inflatable penile prosthesis (IPP) reservoirs has been reported by urologists as a cause of autoinflation. The concept of CC occurring around IPP cylinders has not been studied. Aims Herein we report a case of CC occurring with nonlength‐expanding IPP cylinders, resulting in an S‐shaped deformity. Main Outcome Measures We sought to report a novel cause of S‐shaped deformity in patients after IPP surgery. Methods We reviewed a recent clinical case and conducted a literature review on capsular scar formation in prosthetic surgery. We also conducted a literature review of the inflammatory cascade related with prosthetic surgery. Results Capsular contracture of nonlength‐expanding cylinders resulting in S‐shaped deformity has not been previously reported. The role of certain inflammatory markers seems to play a common role of capsular contracture in the penis and other prosthetic implantation sites. Conclusions Capsular contractures around the cylinders of an IPP can cause deformity, even in patients who have appropriately sized, nonlength‐expanding cylinders. A better understanding is needed regarding the mechanical properties of the tunica albuginea and the inflammatory cascade associated with penile implant surgery. This case represents an argument for early and aggressive postoperative inflation of the IPP. Future studies should evaluate the role of inflammation modulators as adjuvant therapy after IPP surgery. Karpman E and Henry G. Capsular contraction with S‐shaped deformity of nonlength‐expanding inflatable penile prosthesis cylinders: Management and prevention strategies. Sex Med 2013;1:95–98.